The Role of Omnichannel Retailing on Customer Retention Mediated by Brand Experience in Cosmetics Retail: SOR Approach - Pranindyasari, Chelsia; Uscha, Cindy Malinda (Journal of Marketing Innovation (JMI), 2025)
The COVID-19 pandemic, which has persisted for over two and a half years, is now entering a recovery phase. During this period, Indonesian consumers have notably adapted their behavior, becoming more technologically savvy. This shift has been further accelerated by technological advancements, leading to the development of omnichannel strategies—integrated channel management models that unify all available customer interaction points. This research investigates the factors that influence customer retention within the context of cosmetic retailers in Indonesia, utilizing the Stimulus-Organism-Response (SOR) theory. The SOR theory is applied to understand customer purchasing behavior in the omnichannel retail environment and to analyze strategies that can enhance customer retention. Data was collected from 172 respondents using a 1-7 Likert scale questionnaire distributed via Google Forms. The study employed quantitative cross-sectional design and purposive sampling, with data analysis conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that five out of seven hypotheses were supported, revealing that omnichannel interaction and individualization have a significant positive impact on sensory, affective, and behavioral brand experiences. Furthermore, these brand experiences were found to significantly influence customer retention in the cosmetics retail sector.